2015
DOI: 10.1371/journal.pone.0122964
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematous and Malignancy Risk: A Meta-Analysis

Abstract: BackgroundPilot studies have estimated cancer incidence in patients with systemic lupus erythematous (SLE). However, the results have been inconclusive. To ascertain the correlation between SLE and malignancy more comprehensively and precisely, we conducted a meta-analysis.MethodsPubMed, the Cochrane Library and Embase databases through June 2014, were searched to identify observational studies evaluating the association between SLE and malignancy. The outcomes from these studies were measured as relative risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
130
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(137 citation statements)
references
References 48 publications
5
130
0
2
Order By: Relevance
“…Epidemiological studies have shown that chronic inflammatory diseases, such as RA and SLE, are associated with increased risk of haematological, cutaneous and solidorgan malignancies [1,2]. Even limited autoimmune dermatological conditions, such as psoriasis, are associated with increased risk of both cutaneous and systemic solid-organ malignancies [3].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown that chronic inflammatory diseases, such as RA and SLE, are associated with increased risk of haematological, cutaneous and solidorgan malignancies [1,2]. Even limited autoimmune dermatological conditions, such as psoriasis, are associated with increased risk of both cutaneous and systemic solid-organ malignancies [3].…”
Section: Introductionmentioning
confidence: 99%
“…The association between lymphoma and SLE has been examined in varied detail and studies have reported an increased incidence of lymphoma in SLE [13]. Immune dysregulation coupled with the use of immunosuppression may account for the increased incidence of cancer (and lymphoma) in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…SLE's association with lymphoma is a well-established phenomenon. A number of studies have reported a higher incidence of lymphoma in the SLE population compared with healthy cohorts [13]. The effects of lymphoma development in SLE and its impact on modifying the disease's natural history are a matter of great interest amongst both clinicians and researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Comparativement à la population générale, l'incidence des hémopathies est plus élevée chez les patients atteints de maladie auto-immune, telle que le syndrome de Goujerot-Sjögren, la polyarthrite rhumatoïde ou le LES, avec un odd ratio de lymphome allant de 4,1 à 5,7 selon les études [3,[5][6][7]. La fréquence des lymphomes chez les patients lupiques varie de 3,2 à 11,4 % [7,8]. Le développe-ment spontané de lymphome chez les modèles murins de lupus (souris NZB/NZW) avait déjà été rapporté, suggérant un risque accru de lymphome chez ces patients [9].…”
Section: Discussionunclassified